Ada's Violin : the Story of the Recycled Orchestra of Paraguay - Hood, Susan 1954-; Comport, Sally Wern (New York : Simon & Schuster Books for Young Readers, 2016)
The true tale of the Recycled Orchestra of Paraguay, an orchestra made up of children playing instruments built from recycled trash.
Includes bibliographical references.
Keywords: Bordados, Ada Maribel Rios -- Juvenile literature; Bordados, Ada Maribel Rios; Orquesta de Instrumentos Reciclados Cateura -- Juvenile literature; Orquesta de Instrumentos Reciclados Cateura; Orchestra -- Juvenile literature. -- Paraguay; Child musicians -- Juvenile literature; Orchestra; Child musicians